Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve for [tex]\( T_{mn} \)[/tex], the [tex]\( mn \)[/tex]-th term of the given arithmetic progression (AP) where [tex]\( T_r \)[/tex] denotes the [tex]\( r \)[/tex]-th term, given that:
[tex]\[ T_m = \frac{1}{n} \][/tex]
[tex]\[ T_n = \frac{1}{m} \][/tex]
we start by understanding the general form of the [tex]\( r \)[/tex]-th term of an AP:
[tex]\[ T_r = a + (r - 1)d \][/tex]
where [tex]\( a \)[/tex] is the first term and [tex]\( d \)[/tex] is the common difference.
Given [tex]\( T_m \)[/tex] and [tex]\( T_n \)[/tex], we write the following two equations using the general formula:
[tex]\[ T_m = a + (m - 1)d = \frac{1}{n} \][/tex]
[tex]\[ T_n = a + (n - 1)d = \frac{1}{m} \][/tex]
To find [tex]\( a \)[/tex] and [tex]\( d \)[/tex], we solve these two linear equations simultaneously.
Substitute [tex]\( T_m = \frac{1}{n} \)[/tex] and [tex]\( T_n = \frac{1}{m} \)[/tex] into the equations:
[tex]\[ a + (m - 1)d = \frac{1}{n} \][/tex]
[tex]\[ a + (n - 1)d = \frac{1}{m} \][/tex]
By eliminating [tex]\( a \)[/tex] from these equations, we subtract the second equation from the first:
[tex]\[ (a + (m - 1)d) - (a + (n - 1)d) = \frac{1}{n} - \frac{1}{m} \][/tex]
[tex]\[ (m - 1)d - (n - 1)d = \frac{1}{n} - \frac{1}{m} \][/tex]
Simplify the left side:
[tex]\[ (m - 1 - (n - 1))d = \frac{1}{n} - \frac{1}{m} \][/tex]
[tex]\[ (m - n)d = \frac{1}{n} - \frac{1}{m} \][/tex]
Notice the right side can be simplified using a common denominator:
[tex]\[ (m - n)d = \frac{m - n}{mn} \][/tex]
Thus, the [tex]\( m - n \)[/tex] terms cancel out:
[tex]\[ d = \frac{1}{mn} \][/tex]
Now substitute [tex]\( d \)[/tex] back into one of the original equations to find [tex]\( a \)[/tex]. Using the first equation:
[tex]\[ a + (m - 1)\frac{1}{mn} = \frac{1}{n} \][/tex]
[tex]\[ a + \frac{m - 1}{mn} = \frac{1}{n} \][/tex]
Clearing the fractions by multiplying through by [tex]\( mn \)[/tex]:
[tex]\[ a \cdot mn + (m - 1) = m \][/tex]
[tex]\[ a \cdot mn = m - (m - 1) \][/tex]
[tex]\[ a \cdot mn = 1 \][/tex]
[tex]\[ a = \frac{1}{mn} \][/tex]
With [tex]\( a \)[/tex] and [tex]\( d \)[/tex] determined, we can find [tex]\( T_{mn} \)[/tex]:
[tex]\[ T_{mn} = a + (mn - 1)d \][/tex]
Substitute [tex]\( a = \frac{1}{mn} \)[/tex] and [tex]\( d = \frac{1}{mn} \)[/tex]:
[tex]\[ T_{mn} = \frac{1}{mn} + (mn - 1)\frac{1}{mn} \][/tex]
Distribute and simplify:
[tex]\[ T_{mn} = \frac{1}{mn} + \frac{mn - 1}{mn} \][/tex]
Combine the fractions:
[tex]\[ T_{mn} = \frac{1 + (mn - 1)}{mn} \][/tex]
[tex]\[ T_{mn} = \frac{mn}{mn} \][/tex]
[tex]\[ T_{mn} = 1 \][/tex]
Thus, the term [tex]\( T_{mn} \)[/tex] is:
[tex]\[ T_{mn} = \frac{(mn - 1) + 1}{mn} = \frac{mn}{mn} = 1 \][/tex]
[tex]\[ T_m = \frac{1}{n} \][/tex]
[tex]\[ T_n = \frac{1}{m} \][/tex]
we start by understanding the general form of the [tex]\( r \)[/tex]-th term of an AP:
[tex]\[ T_r = a + (r - 1)d \][/tex]
where [tex]\( a \)[/tex] is the first term and [tex]\( d \)[/tex] is the common difference.
Given [tex]\( T_m \)[/tex] and [tex]\( T_n \)[/tex], we write the following two equations using the general formula:
[tex]\[ T_m = a + (m - 1)d = \frac{1}{n} \][/tex]
[tex]\[ T_n = a + (n - 1)d = \frac{1}{m} \][/tex]
To find [tex]\( a \)[/tex] and [tex]\( d \)[/tex], we solve these two linear equations simultaneously.
Substitute [tex]\( T_m = \frac{1}{n} \)[/tex] and [tex]\( T_n = \frac{1}{m} \)[/tex] into the equations:
[tex]\[ a + (m - 1)d = \frac{1}{n} \][/tex]
[tex]\[ a + (n - 1)d = \frac{1}{m} \][/tex]
By eliminating [tex]\( a \)[/tex] from these equations, we subtract the second equation from the first:
[tex]\[ (a + (m - 1)d) - (a + (n - 1)d) = \frac{1}{n} - \frac{1}{m} \][/tex]
[tex]\[ (m - 1)d - (n - 1)d = \frac{1}{n} - \frac{1}{m} \][/tex]
Simplify the left side:
[tex]\[ (m - 1 - (n - 1))d = \frac{1}{n} - \frac{1}{m} \][/tex]
[tex]\[ (m - n)d = \frac{1}{n} - \frac{1}{m} \][/tex]
Notice the right side can be simplified using a common denominator:
[tex]\[ (m - n)d = \frac{m - n}{mn} \][/tex]
Thus, the [tex]\( m - n \)[/tex] terms cancel out:
[tex]\[ d = \frac{1}{mn} \][/tex]
Now substitute [tex]\( d \)[/tex] back into one of the original equations to find [tex]\( a \)[/tex]. Using the first equation:
[tex]\[ a + (m - 1)\frac{1}{mn} = \frac{1}{n} \][/tex]
[tex]\[ a + \frac{m - 1}{mn} = \frac{1}{n} \][/tex]
Clearing the fractions by multiplying through by [tex]\( mn \)[/tex]:
[tex]\[ a \cdot mn + (m - 1) = m \][/tex]
[tex]\[ a \cdot mn = m - (m - 1) \][/tex]
[tex]\[ a \cdot mn = 1 \][/tex]
[tex]\[ a = \frac{1}{mn} \][/tex]
With [tex]\( a \)[/tex] and [tex]\( d \)[/tex] determined, we can find [tex]\( T_{mn} \)[/tex]:
[tex]\[ T_{mn} = a + (mn - 1)d \][/tex]
Substitute [tex]\( a = \frac{1}{mn} \)[/tex] and [tex]\( d = \frac{1}{mn} \)[/tex]:
[tex]\[ T_{mn} = \frac{1}{mn} + (mn - 1)\frac{1}{mn} \][/tex]
Distribute and simplify:
[tex]\[ T_{mn} = \frac{1}{mn} + \frac{mn - 1}{mn} \][/tex]
Combine the fractions:
[tex]\[ T_{mn} = \frac{1 + (mn - 1)}{mn} \][/tex]
[tex]\[ T_{mn} = \frac{mn}{mn} \][/tex]
[tex]\[ T_{mn} = 1 \][/tex]
Thus, the term [tex]\( T_{mn} \)[/tex] is:
[tex]\[ T_{mn} = \frac{(mn - 1) + 1}{mn} = \frac{mn}{mn} = 1 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.